Sustenance signifying Tawheed: دلالة الرِّزْق على التوحيد (المجلة العربية للعلوم و نشر الأبحاث, 2018)
The relation of the subject of sustenance to a great pillar of Islamic religion, which is the belief in the unseen as said by the Almighty: "And in heaven is your Sustenance, as (also) that which you are promised. " [Adh- Dhaariyat: 22], confirms to us the importance of the study of the subject of sustenance in the Holy Quran and Sunnah and the description of a Muslim believing in it.This research, entitled "Sustenance signifying Tawheed", focuses on the sustenance signifying the three types of Tauheed or the belief in Oneness of Allah: al- Rububiyyah (Oneness of Allah’s Lordship), al- Uluhiyyah (Oneness of Worship), and al- Asma’ wal- Sifat (Oneness of Allah’s Names and Attributes) through the presentation of Quranic verses and prophetic traditions related to the subject of sustenance.In reviewing these verses and ahaadeeth, we have seen the clarity of the doctrine of Ahl al- Sunnah wa al- Jama'ah, the ease of its explanation, the abundance of evidence on it, the perfection of Godliness, the restriction of worship to Him and the proof of Allah’s beautiful names and Attributes.And, therefore, this refutes those who find doubts and faults in such matters.Thus, if we study and investigate the significance of sustenance on the rest of the issues of faith, strong faith and its safety from suspicions will appear clear to us.